1901 Nev. Stat. 103, ch. 97, § 17, pt. 6. - (:unkn) unknown (General Publisher, 1901)
The City Council Shall have power . . . [t]o regulate or prohibit the storage of gunpowder and other explosives or combustible materials within the city.
--
Keywords: GUN POWDER STORAGE